Factors influencing anxiety in preoperative patients at RSUD Lasinrang Kab. Pinrang - Sukri; Agustina; Bonggalola (TOUR HEALTH JOURNAL, 2022)
Background: Surgery as a potential or actual threat to someone that can produce psychological and physiological stress reactions. Anxiety is the most dominant psychological condition that occurs in preoperative patients which results in not carrying out or canceling the operation itself. Purpose: The purpose of this study was to determine the relationship between characteristics (Age, Education, Knowledge) with the level of anxiety in preoperative patients. Method: This  research  is  a  correlation  analytic  study  with  a cross sectional approach. The research population is all patients who will undergo surgery at Lasinrang General Hospital, Pinrang Regency. The sampling technique   used accidental sampling  as  many  as  73  respondents. Data  collection  using  a questionnaire  and  data  analysis  methodsusing  Chi-square  with a significance level of 0.05. Result: The results showed that most of the respondents in the adolescent category were 31 respondents (42.5%), most of them had  low education  as  many  as  47  respondents  (64.4%),  and most of the respondents had sufficient knowledge as many as 50 respondents (68.5%). The results of the Chi-Square test showed that  there  is  a  relationship  between  education  (p  0.001)  and knowledge  (p  0.001) with  the  level  of  anxiety  of  preoperative patients and there is no relationship between age with preoperative anxiety level (p 0.618). Conclusion: There  is  a  relationship between education  and knowledge with preoperative anxiety levels at Lasinrang General Hospital, Pinrang Regency. The results of this study are expected to be used as input to improve nursing services, which in  turn  can  reduce  the  level of anxiety of patients who will face surgery.